ANALISIS PERAN INTERGRITAS MANAJEMEN DALAM PENETAPAN TINGKAT MATERIALITAS - F. Ahmad Kurniawan (InFestasi, 2011)
Audit of financial statements intended to obtain reasonable assurance that financial statements are free of material misstatement. Auditor in planning and implementing audit concern with the problem material financial statement and not responsibility for error or deception is not material to the financial statements. Management integrity as principal support of quality control environment and the primary elements internal control that could affect the auditor’s decisions in the determination of materiality. Integrity is the ethical standard in the institution include management action to reduce or elimination the urge and temptation that my cause personnel to act dishonest, illegal or unethical. Though a qualitative methodology, researcher conduct studies on the role integrity management in the determination level of materiality. The research was conducted three stages, stages a thorough exploration, focus exploration and confirmation phase. Analysis of data with the logic of pairing patterns approach (Yin, 2002:140) include analysis domain and taxonomic analysis. Based on the results of research that integrity management is not major consideration in the determination of materiality.